MUPIROCIN RESISTANCE IN METHICILLIN RESISTANTSTAPHYLOCOCCUS AUREUS - J.W.BANERJEE JOHN; ABHISEK ROUTRAY; RADHA MADHAVAN (International Journal of Pharma and Bio Sciences, 2013)
Mupirocin is the topical antimicrobial agent which is used for the treatment of methicillin resistant Staphylococcus aureus (MRSA). However the prevalence of mupirocin resistance in MRSA has increased with the extensive and widespread use of this agent in hospital settings. The present study was attempted to evaluate the low level and high level resistance to mupirocin in MRSA isolates by different phenotypic and genotypic methods. Isolates of MRSA were collected from different clinical specimens obtained from SRM hospital and were identified by routine biochemical reaction. Resistance to mupirocin was determined by Kirby Bauer disc diffusion method (using 5µg mupirocin) as per CLSI guidelines. Low level and high level resistance to mupirocin was confirmed by minimum inhibitory test (MIC) using agar dilution method and comb test. The presence of mupA gene in resistant strains of MRSA was confirmed by PCR method. Among 75 MRSA isolates, 16(21.3%) were mupirocin resistant. Based on MIC (comb test ) 9 (12%) showed low level resistance and 7(9.3%) showed high level resistance to mupirocin.Mup-A gene was present in all the 16 strains.